2002
DOI: 10.1124/jpet.102.039669
|View full text |Cite
|
Sign up to set email alerts
|

Poly(ethylene glycol)-Coated Hexadecylcyanoacrylate Nanospheres Display a Combined Effect for Brain Tumor Targeting

Abstract: The aim of the present study was to evaluate the tumor accumulation of radiolabeled long-circulating poly(ethylene glycol) (PEG)-coated hexadecylcyanoacrylate nanospheres and non-PEG-coated hexadecylcyanoacrylate nanospheres (used as control), after intravenous injection in Fischer rats bearing intracerebrally well established 9L gliosarcoma. Both types of nanospheres showed an accumulation with a retention effect in the 9L tumor. However, long-circulating nanospheres concentrated 3.1 times higher in the glios… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
128
1
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 221 publications
(133 citation statements)
references
References 35 publications
(36 reference statements)
3
128
1
1
Order By: Relevance
“…PEG-coated nanoparticles accumulate in brain tissue more effectively than non-PEG-coated nanoparticles, and those coated with high density PEG also display greater diffusion through brain parenchyma [4,16]. Of high relevance for clinical applications, PEG-coated nanoparticle accumulation is enhanced in pathological foci including gliosarcoma and Multiple Sclerosis models [17,18], possibly due to inflammation-induced BBB hyperpermeability -similar to enhanced nanoparticle permeability/retention (EPR effect) in brain tumors [19]. [20,21] exhibiting dramatically more rapid/extensive nanoparticle uptake than all other neural subtypes, in vitro [22] and in vivo [23].…”
Section: Introductionmentioning
confidence: 99%
“…PEG-coated nanoparticles accumulate in brain tissue more effectively than non-PEG-coated nanoparticles, and those coated with high density PEG also display greater diffusion through brain parenchyma [4,16]. Of high relevance for clinical applications, PEG-coated nanoparticle accumulation is enhanced in pathological foci including gliosarcoma and Multiple Sclerosis models [17,18], possibly due to inflammation-induced BBB hyperpermeability -similar to enhanced nanoparticle permeability/retention (EPR effect) in brain tumors [19]. [20,21] exhibiting dramatically more rapid/extensive nanoparticle uptake than all other neural subtypes, in vitro [22] and in vivo [23].…”
Section: Introductionmentioning
confidence: 99%
“…The first would be targeting brain tumors with therapeutic drugs given that most tumor blood vessels are more permeable and ''leaky'' in comparison to well built vessels in normal tissues. Conceivably the nanoparticles carrying antineoplastic drugs would reach brain tumors, and PEG-coated nanoparticles were found to be with more than 10 times of efficiency in delivery tested by accumulation in tumor tissues when compared to routine delivery through circulation (Brigger et al 2002;Feng et al 2004). Also, the polysorbate coated nanoparticles that can be taken up by brain endothelial cells have been shown to target tumor tissues efficiently (Alyautdin et al 1997).…”
Section: Different Routes For Brain Drug Delivery With Nanotechnologymentioning
confidence: 99%
“…PEGylatingliposome vectors that target the brain's insulin receptor shows promising results for gene therapies [7], as studies in human and rat glioma cells have shown that targeting the insulin receptor yields 100-200 fold higher levels of gene expression as compared to targeting the human epidermal growth factor receptor (EGFR) or the rat transferrin receptor [8]. In addition, hexadecylcyanoacrylate nanoparticles coated with PEG were shown to target rat gliosarcoma cells and accumulate within the cells [9]. PEGylated micelles were shown to accumulate into rat brain glioma models [10].Furthermore, PEG-complexed nanoparticles were shown to permeate the BBB to therapeutically effect models of multiple sclerosis [3,11] and Parkinson's disease [12] among other diseases.…”
Section: Peg-coated Nanoparticlesmentioning
confidence: 99%